BODY PIERCING DALAM KARYA GRAFIS DENGAN TEKNIK CETAK TEMBUS - RAHMAT FERNANDO A, Drs. Irwan, M. Sn., Drs. Yusron Wikarya, M.Pd. (Serupa The Journal of Art Education, 2019)
The creation of this final work aims to visualize body piercing as a concept of graphic artwork. Visualization of the work displays the negative effects of body piercing. The method and process of the works used in the creation of works, through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of concepts, (5) finising. The results of the discussion are a visualization of the negative effects of body piercing. As for the works produced, consisting of ten graphic art works with translucent printing techniques with the titles: Penyesalan, Direnggut, Future, Menarik ?, Mati Rasa, Masokis, Beban, Tak Lazim, Dikucilkan, Terlena.Kata Kunci: Body Piercing, karya, seni grafis,cetak tembus